EFEKTIVITAS MEDIA KOMIK STRIP DIGITAL INTERAKTIF UNTUK MENINGKATKAN MEMBACA PEMAHAMAN LITERAL BAGI ANAK KESULITAN MEMBACA - Zhafirah, Rifdah; Marlina, Marlina; Damri, Damri; Sopandi, Asep Ahmad; Zulmiyetri, Zulmiyetri; Taufan, Johandri; Arnez, Gaby; Handayani, Endang Sri (STKIP Pesisir Selatan, 2025)
The problem underlying this research is that many students are still unable to understand the reading they read. So, with the child's inability to read literal comprehension affects the child's learning outcomes. The purpose of this study was to determine the effectiveness of interactive digital comic strip media to improve literal reading comprehension for children with reading difficulties. The study was conducted using an experimental research type in the form of a single subject study with an A-B-A design. The data analysis technique was in the form of visual graphics and the research instruments were in the form of oral and written tests. Where in the baseline data collection (A) is the child's initial ability to read literal comprehension, Intervention (B) is the ability to read literal comprehension when the treatment was given, and the second baseline data (A2) is the child's ability to read literal comprehension when the treatment was withdrawn. The results of the study showed that there was a significant increase in the ability to read literal comprehension after being given treatment in the form of interactive digital comic strip media. This shows that interactive digital comic strip media is effective for use in learning literal reading comprehension for children who have reading difficulties. Improvements occurred both in terms of the amount of information understood, the ability to remember the contents of the reading, and the accuracy of answering literal questions.